KONSTRUKSI TEMPAT-TEMPAT DI ASIA DALAM MAJALAH MASKAPAI PENERBANGAN Analisis Isi Mediasi Ruang dan Pengalaman Keruangan di Majalah Maskapai Penerbangan Airasia Travel 3 Sixty - Raisa Hashina Rosalini (Jurnal Komunikasi, 2018)
In-flight magazine mediated space or place to experience of tourism. Then the mediation was contruct of place or space. This study aims to analyze construction of place and models of tourism experience in Asia in the Travel Log rubric, Travel 3Sixty in-flight magazine. The data was analyzed with content analysis method. The result shows that Asia is constructed as a friendly culture place that can provide experience of authentic experience. The research also show that in-flight magazine is a new media which can construct local element into a global element.Keyword : in-flight magazine, mediating place, communication geography, content analysis, construction of Asia.